Unraveling the Role of Empathy and Critical Life Events as Triggers for Social Entrepreneurship - Lambrechts, Wim; Caniëls, Marjolein C. J.; Molderez, Ingrid; Venn, Ronald; Oorbeek, Reinke (Frontiers in Psychology, 2020)
Social entrepreneurs are generally believed to have started their venture to improve societal needs and create social value. Yet, in order to achieve continuity of their organization, they need to generate economic value as well. These seemingly opposite objectives of social and economic value creation can cause tensions in social enterprises. This study aims to derive in-depth insights into personal dispositions and motivations of social entrepreneurs, with a specific focus on empathy. The study assesses differences in motivations of social entrepreneurs, and how moral empathy helps them to cope with tensions that arise from trying to achieve both commercial and social goals. Analysis of semi-structured interviews with 33 social entrepreneurs in Belgium, explores the tension between social and economic objectives as a paradox social entrepreneurs have to deal with. First, empathy is an important motivator, but not for all entrepreneurs. Social entrepreneurs who are driven by empathy often indicate that experiencing a critical life event has led to certain business choices. The life event does not always directly lead to increased empathy, but often changes an entrepreneur’s career or life path. Second, while social entrepreneurs are supposed to stress social impact, some respondents firmly state that financial impact is more important to their organization. The results show that social entrepreneurs display other motivations that are typical for ‘traditional’ (commercial) entrepreneurs as well, such as self-realization and the sense of doing meaningful work. Empathy seems to play an important role in successfully dealing with the paradox and tensions between social and economic value creation, and more specifically to prevent mission drift.